The Serum Biomarkers in Ulcerative Colitis - Semih SEZER; Selim DEMIRCI; Melisa Irem KARA; Murat KORKMAZ (Medeniyet Medical Journal)
Objective: In this study, the aim was to evaluate the diagnostic effectiveness of more easily applicable and cost-effective serum biomarkers, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), C-reactive protein (CRP) to albumin ratio (CAR), and CRP-to-lymphocyte ratio (CLR), instead of the endoscopic activity index (EAI) used to determine disease activation in ulcerative colitis (UC) patients. Methods: Blood tests performed during the same period as colonoscopy were reviewed, and NLR, PLR, CAR, and CLR values were calculated. Based on the EAI score, patients with a score <4 were classified as having UC in remission, those with a score ≥4 as having active UC, and those with normal colonoscopy results as the control group. Results: The study included 66 patients with active UC, 31 with UC in remission, and 99 controls. The CLR and CAR values of active and remission UC patients were found to be higher compared with the control group (p<0.001), while no significant difference was found between the groups in terms of PLR and NLR values (p>0.05). The AUC calculated for CLR in diagnosing active UC was significant (p<0.001), and the best cut-off value was determined as >1,75. For CAR, the best cut-off value was calculated as >0.11. Conclusions: This study demonstrated that the CLR and CAR had high sensitivity and specificity for detecting UC activity, whereas the PLR and NLR had low diagnostic value.